A preview on the conceptualization of contemporary knowledge from Islamic Knowledge Management perspective - Hj. Yaakub, Muhamadul Bakir; Othman, Khatijah (2013)
The philosophy of knowledge is known as an established discipline both from Islamic perspective and Western view point.